Seric status of vitamin D among nulligest women at the general reference hospital of Panzi in Democratic Republic of the Congo - Balungwe, Sifa; Maroyi, Raha; Joyeux, Mpakanyi; Omari, Mukango; Philémon, Mulongo; Nyakiyo, Olivier (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Vitamin D has both bony and extra bony implications. The objective of this study was to determine serum vitamin D levels in non-breastfeeding women aged 20 to 35 years. Methods: A cross-sectional study was conducted at the Panzi General Reference Hospital in the Democratic Republic of Congo (DRC) with an occasional sample of 412 nulligest women sensitized during gynecological consultations. A vitamin D test was performed using the immunofluorescence technique and a trans-abdominal ultrasound was routinely performed. Vitamin D deficiency was defined by a serum level ≤29 ng/dl. Data were collected using a pre-established survey questionnaire. Results: The mean age of the women was 25.23±4.54 years. The serum vitamin D level was 77.2% too high, indicating vitamin D deficiency in our context. The nulliparous, students and overweight women were the most encountered. Women who consumed more red meat, green vegetables and alcohol were more affected. Pelvic pain, pelvic pain and bleeding between periods dominated the clinical picture. Conclusions: The serum level was very high in nulligest women aged 20 to 35 years. The study recommends expanded screening and vitamin D supplementation for the prevention of myomas and other conditions in nulligest women.